Since there went the implementation of the integrated system of financial information in the state entities (2015)
The Integrated Financial Information System SIIF Nation was created basically to consolidate the financial information of the entities which are part of the general budget of the nation in the central and decentralized part, to reach to achieve the efficiency, efficacy and effectiveness management of the resources of the nation, in the same way this system is composed of a series of modules, which work together for a more consistent, as are the financial profiles, budget profiles and profiles cash in which all are part of the basic budget chain, which is part one certificate request budget availability, continuing a budget record, which is used to make a payable, then performing an obligation and to end this chain one pay order; considering that not only these transactions can occur, just as the system daily with updates and requests made by each entity, it is improving and responding to some gaps which may occur.